A green, simple and efficient vortex-assisted spraying-based microextraction method for the trace determination of bixafen in rice flour by HPLC-UV - Gosterisli, Tugce Unutkan (ELSEVIER, 2025)
This study introduces an alternative technique for extracting fungicide bixafen from rice flour samples using spraying-based fine droplet formation liquid-phase microextraction (SFDF-LPME). The determination of bixafen was performed using high performance liquid chromatography-ultraviolet detection (HPLC-UV). All chromatographic and extraction parameters that affect the extraction efficiency have been optimized. The reliability of the proposed method was confirmed by obtaining satisfactory relative standard deviation (5.3%), good linearity (R2 = 0.9994), low limits of detection (1.11 mu g/kg) and quantification (3.72 mu g/kg), and acceptable extraction recoveries (76.7-108.2%). The applicability of the method was demonstrated by analyzing spiked rice flour samples. The method's applicability was verified evaluating rice flour samples that spiked with known concentrations of the target compound. Furthermore, the proposed technique minimizes solvent usage, supporting sustainable and green chemistry practices.
Keywords: Bixafen; Spraying-based fine droplet formation liquid phase microextraction; High performance liquid chromatography; Rice flour; CHROMATOGRAPHY; VEGETABLES; RESIDUES; FRUITS; WATER; Chemistry